2017
DOI: 10.1103/physrevb.96.125434
|View full text |Cite
|
Sign up to set email alerts
|

Normal and skewed phosphorene nanoribbons in combined magnetic and electric fields

Abstract: The energy spectrum and eigenstates of single-layer black phosphorous nanoribbons in the presence of perpendicular magnetic field and in-plane transverse electric field are investigated by means of a tight-binding method and the effect of different types of edges is analytically examined. A description based on a new continuous model is proposed by expansion of the tight-binding model in the long-wavelength approximation. The wavefunctions corresponding to the flatband part of the spectrum are obtained analyti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Ey = 30 mV/Å) along the width. In figure 5 we observe the band structure, the conductance and the DOS in the presence of Ey which are in agreement with [12,31]. It is observed that the transverse electric field causes upward and downward shift of energy for valence and conduction sub bands, respectively.…”
Section: Resultssupporting
confidence: 77%
“…Ey = 30 mV/Å) along the width. In figure 5 we observe the band structure, the conductance and the DOS in the presence of Ey which are in agreement with [12,31]. It is observed that the transverse electric field causes upward and downward shift of energy for valence and conduction sub bands, respectively.…”
Section: Resultssupporting
confidence: 77%
“…Furthermore, the difference in physical properties has potential applications. For instance, the control of external electric and magnetic fields on the electronic structure [47] and the coupling and manipulation of the edge states in multilayer PNRs [48]. However, the existed studies have only involved PNRs with above mentioned few particular edge geometries.…”
Section: Introductionmentioning
confidence: 99%
“…It is the case for thin layers of materials with anisotropic band structures, among which black phosphorene is a remarkable example, showing a large band gap and interesting optical, electrical, mechanical, and thermal properties [24]. Similar to other 2D materials with a hexagonal lattice, phosphorene nanoribbons can be fabricated with various skewed and regular zigzag or armchair edges, all of which differ in their electronic structures and transport properties [25]. Nanoribbons with regular zigzag edges host flat-band edge states near the center of the band gap, and therefore, have metallic properties.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, nanoribbons with regular armchair edges have no in-gap states and are insulating without an external field. Regardless of the edge type, nanoribbon electronic and transport properties can be tuned by applying an electric field [25].…”
Section: Introductionmentioning
confidence: 99%